Study on the Maintenance Level of Heritage Buildings in Sandakan, Sabah - Shao Dong, Pang; Mat Radzuan, Indera Syahrul; Shamsudin, Zarina; Ismon, Nur Yuhanis (Research in Management of Technology and Business, 2025)
This research analyses the current maintenance level on heritage buildings and the maintenance impacts on heritage buildings. There are six heritage buildings within the Sandakan Heritage Trail that have been selected as the case study. While two methods adopted in this research to collect data in which the qualitative and quantitative. The triangulation method was used to ensure the reliability and validity of the findings by cross-verifying data from these multiple sources. Thought interviews with related individuals or parties, surveys on visitors and the heritage buildings observation, the data collected for analysis purposes. The findings is to determine the currents maintenance level and evaluate the maintenance impacts on heritage buildings in Sandakan, Sabah.